The impact of environmental politics in overall decision making at national and international levels - İzci, Rana (My University, 2004)
This study aims to explicate the role and impact of environmental politics on the decision-making at both national and international levels pertaining to the perception of environment and to inspire meticulous studies on the link between environmental values and politics particularly in Turkey. Since the ancient times, the relationship between the physical environment and human beings are a matter of concern in politics. Yet, how we coin the term environment, affect our political, social and economic attitudes, perceptions and preferences. More often than not environment is considered within the framework of national wealth, opportunity and conflict of interests at all levels of decision-making process whether national or international. Nevertheless today environmental indicators show that such perceptions of environment and related decisions, policies and preferences trigger global environmental challenges such as global climate change which are likely to jeopardize the human existence and civilization. To put it briefly and clearly it seems that we are living in the imagined environments in which we contemplate residing immune to the consequences of environmental degradation or change. Global environmental challenges and particulary the global climate change force us to rethink our perceptions with regard to environment. Environment is itself a very packed concept and touch upon the very essence of human civilisations in many different ways. It contains immense challenges to the old established and deep seated terms, perceptions and viewpoints which provide futile solutions to the ever lasting and ever growing a number of problems. Although the impact of environmental politics on decision making at both national and international levels is, hence, self-evident environment still is confined to terms which denotes negative conditions such as threat, risk, conflict, and problem and to some extent to security. Drawing from such assessments, old conceptions of geopolitics seem to dominate the world politics leading no way out but acceleration of the environmental change and its impacts. Accordingly prima face approaches and/ or changes in the perception of environment and environmental politics only lead to the deadlocks or at best temporary remedies and solutions. Even if a radical change with regard to environment and related concepts does not occur, global climate change might be stopped. In that case it is, however, more likely to reappear in disguise and in more intimidating forms and magnitudes in a very near future.

Bu tezin amacı çevre siyasetinin karar alma süreçlerindeki etkisini küresel iklim değişikliği örneğinde çevreye yüklenen anlamlar ve çevresel değerler temelinde değerlendirmek ve bu konu çerçevesinde özellikle Türkiye'de çevre siyaseti ve çevresel değerler ilişkisini irdeleyen çalışmalara da kaynak oluşturmaktır. Geçmişten bugüne doğal fiziki çevre ve insanın bu çevre ile olan ilişkileri farklı şekillerde siyaset biliminin konuları arasında yer almıştır. Ulusal ve uluslararası düzeylerde doğal fiziki çevreyi oluşturan canlı ve cansız ögeler pekçok kez zenginlik, fırsat ya da çatışma çerçevesinde ele alınmıştır.Ulusal veya uluslararası siyasi ve ekonomik tercihler de bu çerçeveler temelinde şekillenmiştir. Bugün küresel iklim değişikliği gibi insan varlığını ve uygarlığını toptan tehdit eden bir sorun ise bizlere aslında hayali fiziki çevrelerde yaşamayı sürdürmeyi seçtiğimizi göstermektedir. Bir başka deyişle her ne kadar tahrip edilirse edilsin her zaman yaşayabileceğimiz bir doğal dengenin var olduğuna inanarak siyasi, ekonomik ve sosyal seçimlerimizi yapmaktayız. Oysaki biyosferi kendi istek ve seçimlerize göre şekillendirme çabalarımız ve / veya hiçe sayan faaliyet ve düşünce kalıplarımız büyük çaptaki çevresel değişimlerin de nedeni olmaktadır. Çevresel değişimlerin de çekişme, savaş, yıkım ile sonuçlanacağı öngörülmekte ve bir dizi senaryolar da üretilmektedir. Bu senaryolara bağlı kalarak ve eski jeopolitik değerler üzerinden gidilerek çevre bir dizi olumsuz anlam yükleme çabalarının altında asıl anlam ve değerini yitirmektedir. Bu nedenle çevresel güvenlik, çevresel tehdit gibi olumsuz nitelikleri barındıran anlamlarla ortaya çıktığında çevre ancak dünya siyasetinde yükselen bir ilgi grafiği yakalamıştır. Bu tarz bir algılayış ise bizi doğru çözümlere ve kararlara götürmemektedir. Bunun en güzel örneği de küresel iklim değişikliğini önlemeye ilişkin ulusal ve uluslararası karar ve arayışlarda kendini göstermektedir. Çevre siyasetinin ulusal ve uluslararası karar alma süreçlerine en büyük etkisi yerleşmiş ve kemikleşmiş ama bir çözüm üretemeyen algılamaları, tanımları ve bakış açılarıyla birlikte çözüm önerilerini değişime zorlamasıdır. Bu değişimler yüzeysel yaşandığı takdirde küresel iklim değişikliği gibi bir sistemik bir sorun da görünüşte çözüme kavuşturulacak fakat farklı şekil ve şiddette tekrar insanoğlunun karşısına çıkacaktır.
Keywords: Arazi ekonomisi; Çevre; Doğal kaynaklar ve enerji; Ekonomi